Malignant melanoma of the uterus: a rare cause of postmenopausal bleeding - Abdul Hamid, Habibah; Raja Gopal, Navarasi S.; Ibrahim, Maryasalwati; Awang Soh, Nor Hashliena; Wan Ghazali, Wan Ahmad Hazim (Mary Ann Liebert, 2017)
Background: Malignant melanoma of the uterus is a very rare disease entity bearing potentially serious consequences with an unpredictable and poor prognosis. Case: A 64-year-old woman who had a longstanding, slow-growing blackish mass of the right big toe for more than a decade, presented with postmenopausal bleeding. Histopathologic examination confirmed the diagnosis of a likely secondary malignant melanoma of the uterus. Results: She was treated successfully without any complications via total laparoscopic hysterectomy and bilateral salpingo-oophorectomy (TLHBSO). Even though malignant melanoma of the uterus has a poor prognosis, the patient was alive and disease-free at a 1-year regular follow-up. Conclusions: A malignant melanoma of the uterus is very rare and has a poor prognosis. However, laparoscopic excision of the uterus and adjacent organs in selected patients could be a superior option, especially in terms of rapid recovery and minimal tumor spillage. A combined multidisciplinary approach is highly recommended for dealing with malignant melanoma–related diseases for optimal care and a better clinical outcome.